Correlations Between Staging and Chemotheraphy Response with Testicular Carcinoma Non-Seminoma at Dr. Soetomo Hospital, Surabaya, Indonesia - Nugroho, Ahmad; Renaldo, Johan; Djatisoesanto, Wahjoe (Folia Medica Indonesiana, 2020)
The purpose of this study to describe patientscharacteristics, correlation between stagingnon-seminomacancer and chemotherapyresponse. Data on age, location of tumor, staging, serum levels of the tumor marker post operative, adjuvant therapy, chemotherapy side effects, and response of patient to chemotherapy were gained from medical records inSoetomo Hospital Surabaya from January 2012 to December 2015, and analyzed with SPSS. Correlation between staging and chemotherapyresponse, correlation primary tumor staging (pT) and Metastasis (M), correlation regional lymph nodes staging (N) and metastasis (M), correlation serum tumor marker and chemotherapy response was proccessed by Spearman correlation test. There were no significant correlation between pT staging and M and no significant correlation between N and M staging. Based on tumor markers (S), mostly patients were S2. There were no significant correlation between the response to chemotherapy and serum tumor marker levels. In category of staging group, the mostare 14 patientsstage III. BEP was the most adjuvant Chemotherapy.Nausea and vomiting were The most complained during chemotherapy. Anemia were the most hematologic side effects of chemotherapy.There are no significant correlation between the staging of non-seminoma and the response to chemotherapy. Conclusion: Non seminoma mostly happened in young males. Non-seminoma responses to chemotherapy. Patients in early stage would give a good response to chemotherapy compared to those with advanced stage. After chemotherapy, evaluation should be done to the patients' complaints and complete blood count to detect side effects.